Independent Component Analysis (ICA) and applications to blind source separation of temporomandibular (TMJ) sound signals - Guo, Yin Chao. (2008)
The thesis is a proposed new method for blind source separation using non-casual filters. It also discussed the problem of BSS in the frequency domain.